The “Conguito”, the “Moro” and the “Gitano”: Multiraciality and the Pervasive Stigmatisation of Racialised Youth in Spain - Ballestín González, Beatriz; Rodríguez-García, Dan; Solana-Solana, Miguel; Bereményi, Ábel (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2025)
Maghrebi Muslims, Black Africans, and Spanish Roma people are possibly the most stigmatised, racialised and discriminated against groups in contemporary Spain, a country with a strong legacy of colonialism and a problematic relationship with diversity. Because mixedness is a crucial test for evaluating the persistence of societal ethnoracial divisions, in this article we analyse the narratives of children and youth of Maghrebi Muslim, Black Afro-descendant and Roma mixed ancestry, looking at how their specific mixed heritage shapes their experiences of discrimination and agency. The qualitative information presented here draws on various recent research projects in Spain on intermarriage, multiraciality and multiethnicity. We show that despite the fact that the mixed-ancestry participants were born and socialised in Spain and have one parent who is an ethnic Spaniard, they nonetheless are perceived as foreigners and are subjected to everyday “othering.” That is, their mixedness does not make the stigma of foreignness disappear. The inclusion in our analysis of participants of Roma (Gitano) ancestry, which is the largest national ethnic minority group in Spain, allows us to uncover different aspects of minority/majority dynamics in Spain and to show how patterns of social exclusion encompass racism, Islamophobia and antigypsyism.
Keywords: mixed youth; multiraciality; identity; belonging; discrimination; racism; racialisation; agency